CmNDB1 and a Specific Domain of CmMYB1 Negatively Regulate CmMYB1-Dependent Transcription of Nitrate Assimilation Genes Under Nitrogen-Repleted Condition in a Unicellular Red Alga - Zhou, Baifeng; Shima, Hiroki; Igarashi, Kazuhiko; Tanaka, Kan; Imamura, Sousuke (Frontiers in Plant Science, 2022)
Nitrogen assimilation is an essential process that controls plant growth and development. Plant cells adjust transcription of nitrogen assimilation genes through transcription factors (TFs) to acclimatize to changing nitrogen levels in nature. However, the regulatory mechanisms of these TFs under nitrogen-repleted (+N) condition in plant lineages remain largely unknown. Here we identified a negative domain (ND) of CmMYB1, the nitrogen-depleted (−N)-activated TF, in a unicellular red alga Cyanidioschyzon merolae. ND deletion changed the localization of CmMYB1 from the cytoplasm to the nucleus, enhanced the binding efficiency of CmMYB1 to promoters of nitrate assimilation genes, and increased the transcripts of nitrate assimilation genes under +N condition. Pull-down assay using an ND-overexpressing strain combined with LC-MS/MS analysis helped us to screen and identify an unknown-function protein, CmNDB1. Yeast two-hybrid analysis demonstrated that CmNDB1 interacts with ND. Similar to ND deletion, CmNDB1 deletion also led to the nucleus localization of CmMYB1, enhanced promoter-binding ratio of CmMYB1 to the promoter regions of nitrate assimilation genes, and increased transcript levels of nitrate assimilation genes under +N condition. Thus, these presented results indicated that ND and CmNDB1 negatively regulate CmMYB1 functions under +N condition in C. merolae.